The Appraisal of Self-Care Agency Scale - Revised (ASAS-R): adaptation and construct validity in the Brazilian context - Bruno Figueiredo Damásio; Silvia Helena Koller (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2013)
This study presents the psychometric properties of the Brazilian version of the Appraisal of Self-Care Agency Scale - Revised (ASAS-R). The sample was made up of 627 subjects (69.8% women) aged between 18 and 88 years (mean = 38.3; SD = 13.26) from 17 Brazilian states. Exploratory factor analysis of part of the sample (n1 = 200) yielded a three-factor solution which showed adequate levels of reliability. Two confirmatory factor analyses of the other part of the sample (n2 = 427) tested both the exploratory and the original model. The analysis of convergent validity using the Subjective Happiness Scale, the Satisfaction with Life Scale, and the 36-item Short Form Health Survey Version 2 (SF-36v2) demonstrated adequate levels of validity. A significant correlation was found between levels of self-care agency and age, level of education and income. The analysis of sample members with chronic disease (n = 134) showed that higher levels of self-care agency indicated lower levels of negative impact of the chronic illness in the individual's everyday life.